2022
DOI: 10.1021/acs.langmuir.2c01192
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Interfacial Nanoparticle Organization through Simulation and Theory: A Review

Abstract: Understanding the behaviors of nanoparticles at interfaces is crucial not only for the design of novel nanostructured materials with superior properties but also for a better understanding of many biological systems where nanoscale objects such as drug molecules, viruses, and proteins can interact with various interfaces. Theoretical studies and tailored computer simulations offer unique approaches to investigating the evolution and formation of structures as well as to determining structure−property relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…In this context, computational simulation methods offer valuable information to understand their properties. Various simulation methods, including Monte Carlo, molecular dynamics, mesoscale simulations, self-consistent mean field theory, and ab initio molecular dynamics methods, have been utilized to study the interfacial properties of nanoparticles . The results from computational simulations can be effectively utilized to validate the experimental results using dry-state, liquid-state, and cryo-TEM-tomography-based 3D structures of nanoparticle assemblies.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…In this context, computational simulation methods offer valuable information to understand their properties. Various simulation methods, including Monte Carlo, molecular dynamics, mesoscale simulations, self-consistent mean field theory, and ab initio molecular dynamics methods, have been utilized to study the interfacial properties of nanoparticles . The results from computational simulations can be effectively utilized to validate the experimental results using dry-state, liquid-state, and cryo-TEM-tomography-based 3D structures of nanoparticle assemblies.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…Molecular dynamics (MD) simulation is used to study the arrangement behavior of surfactants, especially the complex system, on the interface and the mechanism of interaction with oil and water at the molecular level, and this process is helpful to effectively understand the oil displacement process and provide theoretical guidance for screening and designing more efficient surfactant. Zhou found that the sulfuric acid groups of the atomic emission spectroscopy (AES) molecules can attract the DTAC molecules in the mixed surfactants, thereby reducing the repulsion between the molecules. DTAC molecules exhibit excellent molecular interface behavior and can improve the arrangement of AES molecules through the interaction between the headgroups.…”
Section: Introductionmentioning
confidence: 99%
“…Fluid–fluid interfaces involving hairy particles also were extensively investigated. , The surface modification changes the contact angle of particles and their adsorption at the interface. Depending on the nature of attached polymers, the interaction of the particle with a fluid interface can vary from repulsive to attractive.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembly of hairy particles at the fluid–fluid interface was also intensively studied. , Numerous experimental works showed that the hairy particles form both disordered monolayers and different 2D structures of a high degree of ordering. The experimental investigations of the assembly of hairy particles at fluid–fluid interfaces were supported by molecular simulations. ,, Grest and co-workers carried out atomistic molecular simulations of hairy particles in solutions and at the liquid–vapor interface. , They observed a spontaneous asymmetry of spherical hairy particles in solutions and at the liquid–vapor interface. They also showed that varying the terminal groups of a nanoparticle canopy strongly alters the coating shape at the water liquid–vapor interface which leads to different assembly morphologies (short linear clusters with a highly aligned structure, dimers, and disordered clumps) .…”
Section: Introductionmentioning
confidence: 99%